An immortalized adipose-derived stem cells line from the PIK3CA-related overgrowth spectrum: Unveiling novel therapeutic targets - Bin Sun; Hongrui Chen; Wei Gao; Yunqi Li; Chen Hua; Xiaoxi Lin (Biochemistry and Biophysics Reports)
PIK3CA-related overgrowth spectrum (PROS) encompasses several rare conditions that lead to overgrowth of various body parts resulting from activating variants in PIK3CA. The absence of ideal cell models significantly impedes progress in PROS research. In this study, we focused on facial infiltrating lipomatosis (FIL) (A disorder within PROS) and aimed to establish and characterize an immortalized PROS cell line. Primary adipose-derived stem cells of FIL were immortal-ized through the transfection of simian virus 40 large T antigen (SV40LT). No significant mor-phological differences were observed in immortalized FIL-ADSCs (Im FIL-ADSCs). Im FIL-ADSCs expressed original mesenchymal surface markers, confirmed by flow cytometry. It harbored PIK3CA mutation and an increased level of PI3K/AKT activation, revealed by sanger sequencing and Western blot respectively. Karyotype analysis revealed a stable chromosome in Im FIL-ADSCs. Higher adipogenic potential and lower osteogenic differentiation properties were de-tected in Im FIL-ADSCs. The proliferative potential of Im FIL-ADSCs increased, whereas malig-nant transformation was not observed in the tumorigenesis assay. Moreover, RNA sequencing further elucidated the role of the transcription factor E2F1 in Im FIL-ADSCs. Drug screening unveiled that STAT3, HSP, EGFR, and NF-kB might be potential therapeutic targets for FIL. This study provided a valuable cellular resource for exploring the underlying pathogenic mechanisms and developing new targeted therapeutic options for PROS.